Implementasi Kemitraan Triple Helix pada Sistem Informasi Pemantauan Covid 19 di Sumatera Selatan: SiPantau Covid-19 - Retnaningsih, Ekowati; Irwan, Irwan; Nuryanto, Nuryanto; Juairiyah, Oktaf; Oktarina, Reni; Komalasari, Oom (Publikasi Penelitian Terapan dan Kebijakan, 2025)
The COVID-19 pandemic, which began in 2020, led to a surge in confirmed cases in Indonesia, reaching 4.2 million by the end of 2021. Transmission occurred largely through the mobility of travelers from high-risk areas to other regions. At that time, Indonesia lacked a digital system to monitor population mobility, and manual tracking methods effectively posed health risks. To address this challenge, the Research and Development Agency of South Sumatra Province initiated applied research to develop a COVID-19 monitoring information system based on a triple helix partnership model (academia, government, and private sector). Using an operational research approach, the study identified key issues: rapid virus transmission, high mobility, absence of a digital monitoring system, and weak inter-actor coordination. Triple helix actors included MDP University, Balitbangda, travelers, transport operators, community leaders, and government officials. Roles were distributed: academia developed the application, the government provided oversight and enforcement, and the public acted as users. The final product consisted of a mobile application for users and field officers, a web-based platform for the control room, and modules for related institutions. The system was piloted and implemented through a Governor's Decree. The triple helix partnership proved effective in developing the monitoring system